2016
DOI: 10.1002/biof.1312
|View full text |Cite
|
Sign up to set email alerts
|

Low nanomolar caffeic acid attenuates high glucose‐induced endothelial dysfunction in primary human umbilical‐vein endothelial cells by affecting NF‐κB and Nrf2 pathways

Abstract: Hyperglycemia contributes to dysregulate endothelial function associated with diabetes, leading to initiation and propagation of vascular complications and dysfunction. Caffeic acid (CA), a dietary hydroxycinnamic acid abundant in coffee, has been reported to exert antidiabetic effects in rat models. Herein, we investigated the molecular effects of physiological concentrations of CA (10 nM) against endothelial dysfunction induced by high glucose (HG) in human endothelial cells (HUVECs). HUVECs were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 39 publications
6
32
0
Order By: Relevance
“…decreases the gLDL-induced secretion of CRP, in good agreement with published data showing that coffee consumption is associated with lower CRP levels in plasma of diabetic or obese women [22,23]. Moreover, CAF decreases the secretion of VCAM-1 and MCP-1 induced by gLDL in HEC, the results confirming previous data showing that CAF decreases inflammation in HEC incubated with resistin or high glucose or in a hyperhomocysteinemia in vivo model by attenuating NF-kB signaling [24][25][26]. We have previously shown that the secretion of VCAM-1 and MCP-1 is stimulated in gLDL-exposed HEC by Caffeic acid decreases oxidative stress in gLDL-exposed HEC.…”
Section: Discussionsupporting
confidence: 91%
“…decreases the gLDL-induced secretion of CRP, in good agreement with published data showing that coffee consumption is associated with lower CRP levels in plasma of diabetic or obese women [22,23]. Moreover, CAF decreases the secretion of VCAM-1 and MCP-1 induced by gLDL in HEC, the results confirming previous data showing that CAF decreases inflammation in HEC incubated with resistin or high glucose or in a hyperhomocysteinemia in vivo model by attenuating NF-kB signaling [24][25][26]. We have previously shown that the secretion of VCAM-1 and MCP-1 is stimulated in gLDL-exposed HEC by Caffeic acid decreases oxidative stress in gLDL-exposed HEC.…”
Section: Discussionsupporting
confidence: 91%
“…However, recent evidences suggest that the selective inhibition of NF‐κB pathway and the activation of an antioxidant adaptive cell response through nuclear factor erythroid 2 (Nrf2) pathway modulation seem to be the main mechanisms by which ACNs can exert their protective effect. In fact, previous data supported the hypothesis of a cross talk between Nrf2 and NF‐κB and particularly of an inhibitory effect of Nrf2/EpRE (Electrophile‐Responsive Element) pathway on NF‐κB transcription machinery (Ferrari et al, ; Fratantonio et al, ; Fratantonio, Speciale, et al, ; Fratantonio, Cimino, Speciale, & Virgili, ; Speciale et al, ).…”
Section: Discussionmentioning
confidence: 66%
“…Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and 18S rRNA were validated as reference genes and they maintained constant expression levels in all conditions and treatments. The specific primers set for the target genes were as follows: 18S rRNA, forward, 5′-GTA ACC CGT TGA ACC CCA TT-3′, reverse, 5′-CCA TCC AAT CGG TAG TAG CG-3′ [16]; GAPDH, forward, 5′-GGC TCT CCA GAA CAT CAT CCC TGC-3′, reverse, 5′-GGG TGT CGC TGT TGA AGT CAG AGG-3′; E-selectin, forward, 5′-CTG CCA AGT GGT AAA ATG TTC AAG-3′, reverse, 5′-TTG GAC TCA GTG GGA GCT TCA-3′ [17]; VCAM-1, forward, 5′-GAA TGG GAG CTC TGT CAC TGT AAG C-3′, reverse, 5′-GAC CAA GAC GGT TGT ATC TCT GGG-3′ [18]; TNF- α , forward, 5′-CCA GGC AGT CAG ATC ATC TTC TC-3′, reverse, 5′-AGC TGG TTA TCT CTC AGC TCC AC-3′ [19]; IL-8, forward, 5′-ACT GAG AGT GAT TGA GAG TGG AC-3′, reverse, 5′-AAC CCT CTG CAC CCA GTT TTC-3′ (Primers Bank ID 10834978a2) [20]. Gene expression was assessed by real-time PCR (Applied Biosystem 7300 Real-Time PCR System, Monza, Italy) coupled with the Sybr green JumpStart™ Taq ReadyMix kit.…”
Section: Methodsmentioning
confidence: 99%